EFEKTIFITAS PENGGUNAAN MEDIA TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM KEMAMPUAN MENYUSUN KALIMAT PADA ANAK TUNARUNGU DI SLB TANJUNGPINANG. - Riasnelly - Riasnelly (Universitas Negeri Padang, 2013)
The research was motivated by the inability of deaf children in developing structured sentences, so the intent and meaning of the sentence that made ​​it difficult to understand by others, which in turn inhibits the deaf child's communication. Therefore, the author tries to use information and communication technology as a medium of learning the Indonesian language in deaf children to help improve ability to construct a sentence is structured. Formulation of the problem in this research is